Sikap Toleransi Petani Kentang Dan Tingkat Adopsi Teknologi Usahatani Kentang - Suci Yulinarti; Muhammad Yuzan Wardhana; Romano Romano (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
Potato is a national superior vegetable commodity that is prioritized for development by the government. Bener Meriah Regency is a center for potato development, supported by climatic conditions suitable for potato growth. However, so far the production of potato plants has not been able to meet Indonesia's domestic needs. This study aims to describe what technologies are applied by potato farmers in Bener Meriah and want to see how the level of technology adoption applied by potato farmers in Bener Meriah Regency is analyzed descriptively qualitatively, statistically, and using crosstabulation. The results showed that the tolerance attitude of potato farmers who used technology in Bener Meriah Regency was included in the high category, namely daring to take risks and having more than two efforts in overcoming the risks of potato farming. The use of technology that has been applied by potato farmers in Bener Meriah is the technology of using superior seeds, cultivation techniques that have followed the recommendations of the extension worker, the use of vegetable pesticides, pest control according to the instructor's recommendations, the use of mulch, hand tractor, sprayer, irrigation, cold storage technology, and good packaging. Then potato farmers who have a high level of technology adoption are more tolerant in facing farming risks.